Unkomplizierte Komplizen - neue Wege der Luft-Schiene-Kooperation. - Sauter-Servaes, Thomas (Deutscher Verkehrs-Verl., 2007)
Integrierte Verkehrsdienstleistungen von Bahnen und Luftverkehrsgesellschaften stellen im Fernverkehr trotz hoher Investitionen in die Schnittstellenoptimierung immer noch ein Nischenprodukt dar. Ein wesentlicher Grund hierfür sind der hohe Komplexitätsgrad intermodaler "seamless travel"-Lösungen und die damit verbundenen Hemmnisse der ungünstigeren Kostenstruktur sowie des höheren Fehlerpotenzials. Ausgehend von der These, dass multimodale Mobilitätslösungen einen wichtigen Beitrag für den Zugang der Schiene zu qualitativ hochwertigen und ertragsstarken Verkehren bieten, werden die ersten Erfahrungen der CNL-SWISS-Kooperation Night&Flight vorgestellt. difu

The study shows that the new 'Night & Flight' service does not easily secure new customers for overnight trains, Instead, it prompts passengers who habitually use night trains, to avail of this mode of travel more extensively. In place of optimizing customer potential, an increase in existing customers' usage of overnight trains has been evident. Air passengers do not feel motivated to take up the new overnight train service offer. Since the business travel market shows strong signs of habitual preference for a particular mode of transport and the number of potential overnight rail travellers is limited, awareness of this new rail service is essential. In spite of the small amount of money spent on advertising, market awareness has been noteworthy. It appears that this innovative form of rail travel has profited from the media's "word of mouth" contribution. It will only be possible to foster long term awareness of this service wherever travellers alternative modes of transport. difu
Keywords: Verkehr; Fernverkehr; Luftverkehr; Eisenbahnverkehr; Verkehrsmittelwahl; Verkehrsdienstleistung; Multimodale Mobilität; Geschäftsreiseverkehr; Fluggesellschaft; Produktinnovation; Akzeptanz